(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this essay, the opinions of the attendees of the Workshop on the Biologic Basis of Modern Endodontic Practice have been collected, correlated, and summarised. The position and review papers presented during the workshop, the consensus of the workshop attendees, and the author’s specific subject-matter experience were combined to create this synthesis.